2018
DOI: 10.3390/en11123449
|View full text |Cite
|
Sign up to set email alerts
|

Modelling a Hypersonic Single Expansion Ramp Nozzle of a Hypersonic Aircraft through Parametric Studies

Abstract: This paper aims to contribute to developing a potential combined cycle air-breathing engine integrated into an aircraft design, capable of performing flight profiles on a commercial scale. This study specifically focuses on the single expansion ramp nozzle (SERN) and aircraft-engine integration with an emphasis on the combined cycle engine integration into the conceptual aircraft design. A parametric study using computational fluid dynamics (CFD) have been employed to analyze the sensitivity of the SERN’s perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 30 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…The FAME aircraft requirements have been previously described by Alkaya et al [14]. The individual component analyses on which this work is based, for ramjet and scramjet compression systems have been reported in [15][16][17] and for nozzle performance in [18,19].…”
Section: Future Supersonic Travelmentioning
confidence: 99%
“…The FAME aircraft requirements have been previously described by Alkaya et al [14]. The individual component analyses on which this work is based, for ramjet and scramjet compression systems have been reported in [15][16][17] and for nozzle performance in [18,19].…”
Section: Future Supersonic Travelmentioning
confidence: 99%
“…Several studies have been conducted to explore the design methods and flow characteristics of 3D asymmetric expansion nozzles. Ridway et al [4] reported that the expansion ramp shape, angle, exit area and cowl shape have a significant effect on the thrust of a single expansion ramp nozzle (SERN). Shenkin et al [5] conducted calculations and experiments to investigate the effect of different schemes of SERN and its main geometric parameters on performance.…”
Section: Introductionmentioning
confidence: 99%